2020
DOI: 10.1049/iet-smt.2018.5393
|View full text |Cite
|
Sign up to set email alerts
|

Robust approach to depth of anaesthesia assessment based on hybrid transform and statistical features

Abstract: To develop an accurate and efficient depth of anaesthesia (DoA) assessment technique that could help anaesthesiologists to trace the patient's anaesthetic state during surgery, a new automated DoA approach was proposed. It applied Wavelet-Fourier analysis (WFA) to extract the statistical characteristics from an anaesthetic EEG signal and to designed a new DoA index. In this proposed method, firstly, the wavelet transform was applied to a denoised EEG signal, and a Fast Fourier transform was then applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Hence, the proposed model can be utilised as a low cost, and a simple model to predict the DoA using single channel EEG signals. [17] Wavelet technique based on Fourier transform EEG Diykh et al, [35] Complex network-based spectrum technique EEG 86 Chowdhury et al, [23]…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the proposed model can be utilised as a low cost, and a simple model to predict the DoA using single channel EEG signals. [17] Wavelet technique based on Fourier transform EEG Diykh et al, [35] Complex network-based spectrum technique EEG 86 Chowdhury et al, [23]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we adopted our previous study to segment EEG signals [ 18 , 19 , 20 , 21 ]. Evidently, the proposed method granted a highly satisfactory classification accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…Experts depend on different techniques to capture brain activity and detect seizures, such as electroencephalograms (EEG) and magnetic resonance imaging (MRI) [ 16 , 17 ]. However, researchers are in favour of EEG for epilepsy diagnosis due to it is low cost; it also provides supportive proof of seizures and assists with detection of epilepsy [ 18 , 19 , 20 , 21 ]. In addition, clinical studies have shown that a seizure can leave signs on a patient’s EEG recording even after it occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Dennis et al [ 6 ] gave a summary review of EEG-based brain–computer interface (BCI) and explored the possibility of enhancing neurorehabilitation of people with strokes and other chronic disorders. Mohammed et al [ 7 ] introduced a new method to represent the depth of anesthesia (DOA) as compared to conventional bispectral index (BIS) monitor using wavelet–Fourier analysis (WFA DOA ) on EEG signal.…”
Section: Introductionmentioning
confidence: 99%